2011
DOI: 10.1111/j.1743-4580.2010.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Women, Land Struggles, and the Reconstruction of the Commons

Abstract: This article examines the question of communal land property in Africa and its implications for women's land rights. Among the themes discussed are: the reforms of communal land tenure attempted by the World Bank in the 1990s, the critique of communal land relations that feminist organizations have made on account of their patriarchal discrimination against women, and the simultaneous efforts by landless rural and urban women to appropriate unused plots of public land for subsistence farming. While warning tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 13 publications
0
41
0
14
Order By: Relevance
“…Feminist historians have linked the devaluation of social reproduction to the historical division of productive and reproductive work in the advent of capitalism (Bock and Duden 1976); the term 'traditional' is therefore misleading. Gender inequalities in countries of the Global South cannot be separated from colonialism and its implementation of a sexual division of labour and the construction and enforcement of gender inequalities (Federici 2011;. The practice of employing female domestic workers from poorer and mostly rural families also has its roots in colonial rule (Meyiwa 2012).…”
Section: Enclosure Through the Commodification Of Social Reproductionmentioning
confidence: 99%
“…Feminist historians have linked the devaluation of social reproduction to the historical division of productive and reproductive work in the advent of capitalism (Bock and Duden 1976); the term 'traditional' is therefore misleading. Gender inequalities in countries of the Global South cannot be separated from colonialism and its implementation of a sexual division of labour and the construction and enforcement of gender inequalities (Federici 2011;. The practice of employing female domestic workers from poorer and mostly rural families also has its roots in colonial rule (Meyiwa 2012).…”
Section: Enclosure Through the Commodification Of Social Reproductionmentioning
confidence: 99%
“…Among the Kodi of Indonesia's eastern island lands, woodlands, fencerows and gullies of other farmers (private holdings, small medium, and large) ' (1996, p. 162). For a more recent discussion of this phenomenon, see (Federici 2011). 21 One wonders if the differing impressions/emphases of myself (a woman) and Suyanto (a man) may also reflect differing perceptions among local men and women (as Behrman et al 2012 found-Ugandan couples studied did not necessarily agree about what they jointly owned).…”
Section: Lands Forest and Ownershipmentioning
confidence: 99%
“…Incorporating a gendered perspective into priority setting has been identified as important for mainstreaming gender in agricultural systems (Meizen-Dick 2010;World Bank 2009) and for improving women's contribution to agricultural production and sustainability (IAASTD 2009). The absence of consideration for gender issues in agricultural policies (Pellizzoli 2010), institutional structures for access to capital and bargaining power (Mohamed 2003;Mpuga 2010;Nina and Sanders 1998) and social norms around appropriate gender roles in division of labor, decision-making, and access to resources and education (Gotschi et al 2009;Nation 2010;Kleinbooi and Lahiff 2007;Federici 2011;Hyder 2005;Katungi et al 2008;Oya and Sender 2009) have been well documented. The impact on women's health (Doss 2001;Loewenson et al 2010), economic stability (Peterman 2011), and food production ) have also been given considerable attention.…”
Section: Gender In Agriculturementioning
confidence: 99%